2016
DOI: 10.1016/j.neuron.2016.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Running Speed Signals in Medial Entorhinal Cortex

Abstract: Grid cells in medial entorhinal cortex (MEC) can be modeled using oscillatory interference or attractor dynamic mechanisms that perform path integration, a computation requiring information about running direction and speed. The two classes of computational models often use either an oscillatory frequency or a firing rate that increases as a function of running speed. Yet it is currently not known whether these are two manifestations of the same speed signal or dissociable signals with potentially different an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
235
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(262 citation statements)
references
References 69 publications
25
235
2
Order By: Relevance
“…This absence of one-to-one correspondence in co-recoded grid and speed cells during gain manipulations raises the important possibility that grid cells integrate input from many speed cells. In line with this idea, several recent works have demonstrated that speed cells show high degrees of heterogeneity, with their firing rates showing positive or negative linear, saturating and even non-monotonic relationships with running speed 7,8,25 . These levels of heterogeneity present a significant challenge for attractor-based grid cell network models, which often require inputs that are positively and linearly modulated by running speed.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This absence of one-to-one correspondence in co-recoded grid and speed cells during gain manipulations raises the important possibility that grid cells integrate input from many speed cells. In line with this idea, several recent works have demonstrated that speed cells show high degrees of heterogeneity, with their firing rates showing positive or negative linear, saturating and even non-monotonic relationships with running speed 7,8,25 . These levels of heterogeneity present a significant challenge for attractor-based grid cell network models, which often require inputs that are positively and linearly modulated by running speed.…”
Section: Discussionmentioning
confidence: 73%
“…Multiple signals in MEC carry information about running speed, the two most prominent being speed cells 7,8,25 and theta oscillations 7,26 . We first analyzed MEC speed cells, which could provide speed-tuned input to grid cells 8 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach employed and the results obtained in the present study are considered to endorse these previous reports. Furthermore, various previous reports [17][18][19][20][21] have suggested an association between changes in exercise speed and improvement in brain function. These findings suggest that physical training that involves being aware of the focused attention (as adopted in this intervention method) is more likely to lead to higher brain activity and improvement in cognitive function than monotonous physical training.…”
Section: Discussionmentioning
confidence: 92%
“…By 2006 it was observed that some information about speed is present in a subset of grid cells, especially in layer III and deeper 187 , but the correlations between firing rate and speed in these cells were weak and would require decoding from large cell numbers to yield a reliable momentary speed signal 166 . We now know that the entorhinal cortex has a distinct population of cells whose firing rates increase linearly with speed 166,209 . In the large majority of speed-tuned MEC cells 166 , firing rates increase linearly as a function of speed, up to 30-40 cm per s in rats.…”
Section: A Zoo Of Cell Typesmentioning
confidence: 99%